This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: (i) k = 1 k 2 k . (ii) k = k ( k + 1 ) 3 k . (iii) k = k 2 2 k . (iv) k = 1 2 k k ( k + 1 ) . 8. Find a power series expansion for f ( x ) = Z x e t 2 dt valid for all x . 9. Suppose a = 1, a 1 = 1, and a n + 2 = a n + 1 + 6 a n for n 0. (a) Find a 2 , a 3 , a 4 . (b) Prove that a n 6 n . (c) Let f ( x ) = n = a n x n . Show that this power series has radius of convergence R 1 6 . (d) Show that f ( x ) = 1 / ( 1x6 x 2 ) . (Hint: This is similar to a previous exercise.) (e) Use partial fractions to write f ( x ) = A 13 x + B 1 + 2 x for some constants A and B . (f) Use the power series expansions of 1 13 x and 1 1 + 2 x to show that a n = 3 5 3 n + 2 5 (2 ) n ....
View
Full
Document
 Fall '10
 BrainPigott
 Calculus

Click to edit the document details